Environmentally specific empowering leadership and organizational citizenship behavior toward the environment: The roles of green work engagement, psychological ownership, and environmental concern - Mankgele, Khutso Pitso; Fatoki, Olawale (Asian Management and Business Review, 2025)
This study investigates the influence of environmentally specific empowering leadership on organizational citizenship behavior towards the environment (OCBE) among employees in hospitality firms. A theoretical framework posits that environmentally specific empowering leadership enhances OCBE, with psychological ownership and green work engagement acting as mediating variables. Furthermore, environmental concern among co-employees moderates this relationship. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyze data collected from 525 mid-level managers working in three- to five-star hotels in the municipalities of Tshwane and Johannesburg using structured questionnaires. The findings confirm that environmentally specific empowering leadership significantly enhances OCBE. Psychological ownership and green work engagement are critical pathways in translating leadership practices into pro-environmental employee behaviors. Additionally, the moderating role of environmental concern underscores the importance of cultivating an organizational culture that values environmental sustainability. The study recommends that hospitality firms embed environmentally focused leadership practices within their organizational structures, emphasizing empowerment and employee engagement to foster pro-environmental behaviors. Policymakers are encouraged to incentivize sustainable leadership practices and provide training programs that equip managers with skills to inspire environmental responsibility among employees. These contributions advance policy and practice by highlighting the strategic role of leadership in promoting sustainability and positioning the hospitality sector as a model for environmentally conscious business operations.